Expert Systems in HRM : A Digital Construction - Primadona; Emrizal (Postgraduate, University of Mataram, 2023)
The main objective of this research is to carefully describe the role of Expert Systems (ES) in human resource management discourse. What logical constructs must be built when there is a desire to empower the capabilities of computational expert systems in their pragmatic use. Human Resource Expert Systems (HRES) can mimic the decision-making capabilities of a Human Resource Expert (HRE). The design and development of HRES depends on top management initiative and support. The implementation of HRES should be holistic, with maximum participation from all departments in the organization.Â This study uses a qualitative descriptive method, with a literature study approach. The main data is drawn from a variety of selected journal papers, taken from reputable journals.Â Other sources that are compatible with the research, such as news, academic papers, videos and other documents. Â The study found that there is a challenge to reduce the fear of computers in HR functions and resistance to change. HRES can increase productivity levels by assisting HR managers in making rational decisions to solve unstructured HR related problems. The emphasis is on organizational change and bold initiatives to further implement ES in the HR domain and overcome challenges. This paper aims to analyse the focus areas of HRES and the functions where HRES faces limitations and challenges.